2014
DOI: 10.2478/pjs-2014-0050
|View full text |Cite
|
Sign up to set email alerts
|

Adenocarcinoma of the Small Bowel – A Case Report

Abstract: The paper presents a rare case of a patient with adenocarcinoma of the small intestine who reported to the hospital due to non-specific gastrointestinal symptoms. Following diagnostic examinations, the patient underwent a surgery. The post-operative period proceeded with no complications. The case presented below confirms the usefulness of imaging examinations (abdominal CT) when pathologies within the small intestine are suspected. An accurate interpretation of the result was an indication for a surgical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
2
0
1
Order By: Relevance
“…Hastalığın tanısında sıklıkla kullanılan görüntüleme yöntemi oral ve/ veya intravenöz kontrastlı bilgisayarlı tomografidir (10). Endoskopik görüntüleme yöntemlerinin (çift balon entereskopi, video kapsül endoskopi gibi) tanı da kullanımlarının sıklığı artmaktadır (11). Ancak bizim vakamızda da olduğu gibi hastaların çoğu cerrahi eksplorasyon esnasında tanı almaktadır.…”
Section: Discussionunclassified
“…Hastalığın tanısında sıklıkla kullanılan görüntüleme yöntemi oral ve/ veya intravenöz kontrastlı bilgisayarlı tomografidir (10). Endoskopik görüntüleme yöntemlerinin (çift balon entereskopi, video kapsül endoskopi gibi) tanı da kullanımlarının sıklığı artmaktadır (11). Ancak bizim vakamızda da olduğu gibi hastaların çoğu cerrahi eksplorasyon esnasında tanı almaktadır.…”
Section: Discussionunclassified
“…The most frequently used and reliable diagnostic exam is contrast-enhanced CT scan with appropriate IV and oral protocols, while non-contrast-enhanced CT scan has an inferior accuracy rate “ [12] .” Many other modalities have also been used. Endoscopic studies, such as double-balloon enteroscopy or video capsule endoscopy, are being increasingly used [13] . Nevertheless, approximately half of the cases are only diagnosed at surgery, mostly because of misdiagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomically, more than half of adenocarcinomas of the small bowel originates from the duodenum. [1][2][3][5][6][7] Incidence rates vary according to geographical location, but in general, the highest rates are seen among those living in North America and Western Europe, while the lowest rates are observed among Asians. 1 Results of tumor phenotyping of small-bowel adenocarcinomas (SBAs) have shown that the molecular aberrations in these tumors are somewhat similar to those seen in colorectal cancers.…”
Section: Introductionmentioning
confidence: 99%